Difficulties in Differentiating Cardiac Lymphoma and Metastasis Based on Radiologic Features: Two Case Reports - Hyun Jae Lim (The Korean Society of Radiology, 2021)
Cardiac tumors are rare diseases with various imaging findings. However, differentiating cardiac tumors based on imaging findings is challenging because of similarities in imaging features. We present two cases of cardiac tumors, including primary cardiac lymphoma and cardiac metastasis, in which the differential diagnosis was difficult.